Methanol in Plant Life - Dorokhov, Yuri L.; Sheshukova, Ekaterina V.; Komarova, Tatiana V. (Frontiers in Plant Science, 2018)
Until recently, plant-emitted methanol was considered a biochemical by-product, but studies in the last decade have revealed its role as a signal molecule in plant-plant and plant-animal communication. Moreover, methanol participates in metabolic biochemical processes during growth and development. Plants generate methanol in the reaction of the demethylation of macromolecules including DNA and proteins, but the main source of plant-derived methanol is cell wall pectin, which is demethylesterified by pectin methylestarases (PME). Methanol emissions increase in response to mechanical damage or other stresses due to trauma to the cell wall, which is the main source of methanol production. Gaseous methanol from the wounded plant induces defence reactions in intact leaves of the same and neighbouring plants, activating so-called methanol-inducible genes (MIGs) that regulate plant resistance to biotic and abiotic factors. Since PME is the key enzyme in methanol production, its expression increases in response to wounding, but after elimination of the stress factor effects, the plant cell should return to the original state. The amount of functional PME in the cell is strictly regulated at both the gene and protein levels. There is negative feedback between one of the MIGs, aldose epimerase-like protein, and PME gene transcription; moreover, the enzymatic activity of PMEs is modulated and controlled by PME inhibitors (PMEI), which are also induced in response to pathogenic attack.